Evaluasi dan Perencanaan Ulang Instalasi Pengolahan Air Limbah (IPAL) Industri Pembekuan Ikan PT. X Kabupaten Sidoarjo - A’yunin, Qurrotu; Afrianisa, Rodu Dhuha (Teknik Lingkungan Universitas Islam Indonesia, 2024)
Fisheries have become one of the main economic sectors in Sidoarjo Regency. X Ltd., an industry producing frozen fish, already has a Wastewater Treatment Plant, but the WWTP effluent produced does not meet quality standards. Based on these problems, it is necessary to evaluate the WWTP and then re-plan the WWTP so that the effluent results meet quality standards. The evaluation method was carried out by analyzing samples of wastewater from each WWTP unit, measuring the dimensions of each WWTP unit, and comparing the detention time parameters with the design criteria. The evaluation results showed that the existing WWTP conditions did not meet the design criteria, and the existing WWTP effluent results did not meet the quality standards of East Java Governor Regulation No. 72 of 2013. The recommendation from the evaluation results is to re-plan the WWTP using an Anaerobic-Aerobic filter system. The units used are screens, equalization tanks, initial settling tanks, anaerobic filter tanks, aerobic filter tanks, and final settling tanks. The WWTP plans to treat wastewater with a discharge of 3 m 3 /day and characteristics of the wastewater, i.e., TSS 179 mg/L, BOD 239 mg/L, COD 586 mg/L, and Ammonia 29 mg/L. The WWT dimension is 6m x 1m x 1.5 m.